Radio-protective effects of ultra-fine bubble hydrogen water and serum protein responses in whole-body radiation-exposed mice - Masaru Yamaguchi; Khin Thandar Htun; Youta Tatara; Yoshiaki Sato; Masato Hosoda; Suchart Kothan; Chikashi Kamimura; Osamu Inanami; Ikuo Kashiwakura (Scientific Reports)
Abstract Many studies have demonstrated hydrogen’s therapeutic and preventive effects on various diseases. Its selective antioxidant properties against hydroxyl radicals, which are responsible for the indirect effects of ionizing radiation, may make it worthy of attention as a new radio-protector. We recently developed new hydrogen water that is more stable and has higher antioxidant activity by using ultra-fine bubbles. In this study, female C57BL/6J mice given ad libitum access to ultra-fine bubble hydrogen water (UBHW) were subjected to whole-body irradiation (WBI) with X-rays, and the radio-protective effect of UBHW was evaluated. WBI with 6.0 Gy (sub-lethal dose) resulted in a 30-day survival rate of 100% in UBHW-fed mice, compared with 37% in control mice. In the case of WBI with 6.5 Gy (lethal dose), while the control mice died out in about 3 weeks, the 30-day survival rate improved to 40% by UBHW due to the high scavenging activity of hydroxy radicals. Twenty-six serum proteins involved in inflammatory and immune responses were significantly identified in UBHW-fed mice by proteomics, and UBHW may enhance and regulate these functions, resulting in reduced damage in mice exposed to WBI. We conclude that UBHW has good potential in radio-protection, with evidence that warrants further research efforts in this field.